FIRST RECORD OF THE BAMBOO SPECIALIST IHERING'S ANTBIRD Myrmotherula iheringi oreni (AVES: THAMNOPHILIDAE), IN THE JUNÍN DEPARTMENT, PERU - VÁSQUEZ-ÁREVALO, Francisco Alción (2024)
Myrmotherula iheringi oreni is a species known for its association with bamboo forest in southern Peru. Its distribution range is restricted to the departments of Madre de Dios, Cusco, Puno, and Ucayali; however, our record of M. iheringi oreni near the town of Poyeni represents the first occurrence for the department of Junín.